PENGARUH TINGGI RENDAHNYA PRODUKTIVITAS MELALUI KUALITAS KEHIDUPAN KERJA - Diasty Widar Hapsari; Indi Djastuti (Jurnal Akuntansi dan Pajak, 2023)
This study aims to determine the effect of work stress and quality of work life on work productivity at SMK Negeri 2 Bawang, Banjarnegara with 94 teachers as respondents. Statistical tests and data processing were carried out using Partial Least Square (Smart PLS 3.0). The research findings show that (1) work stress has a negative and significant effect on work productivity; (2) work stress has a negative and significant effect on the quality of work life; (3) that the quality of work life has a positive and significant effect on work productivity. Key Words: Work Stress, Work Productivity, Quality of Work Life